PENGARUH HARGA, INFLASI, NILAI TUKAR DAN PENDAPATAN PERKAPITA TERHADAP VOLUME EKSPOR KERTAS INDONESIA TAHUN 2002-2014 KE JEPANG, HONGKONG, TAIWAN, SINGAPURA, AUSTRALIA - Ina Tutus Nur Istiafani; Nenik Woyanti (BISECER (Business Economic Entrepreneurship), 2019)
ABSTRACT               The large decline in demand for paper exports in 2014 occurred in the main destination countries of paper exports became an obstacle. The paper exports fell by 3.22% in 2014. Not only paper, but the fluctuations of paper pulp exports also fell by 6.74% in the same year. Countries such as Japan, Hong Kong, Taiwan, Singapore and Australia exprerience a significant decline. The unstable price of paper causes the volume fluctuations of paper exports. Another obstacle in paper demand was the increase of exchange rate volaitility of the export destination countries.. Inflation in export destination countries causes a decline in paper exports. The growth rate of Gross Domestic Product (GDP) per capita will reflect the opportunity for paper exports in the destination country.This study aims to analyze the impact of price, inflation, exchange rate volatility and income rate towards the Indonesian paper volume exports to Japan, Hong Kong, Taiwan, Singapore and Australia in 2002 – 2014. This study used primary data in the form of panel data. This research used multiple linear regression analysis using E-views as the method of collecting data.Based on the results, it can be concluded that the price variable, exchange rate and income rate have a positive and significant impact, while the inflation and volatility variable have a negative and unsignificant impact towards the Indonesian paper volume exports to Japan, Hong Kong, Taiwan, Singapore, and Australia in 2002 – 2014. Keywords: volume of Indonesian paper exports, prices, inflation, exchange rates, production Keywords: volume of Indonesian paper exports, prices indeks, inflation, exchange rates, income